Antisemitism in Galicia: agitation, politics, and violence against Jews in the late Habsburg monarchy - Buchen, Tim (Austrian and Habsburg studies, 2020)
List of Illustrations -- Preface to the English Edition -- Introduction -- Chapter 1. Agitation -- Chapter 2. Violence -- Chapter 3. Politics -- Chapter 4. Summary -- Epilogue -- Bibliography --